Ice core processing at Dome Fuji Station, Antarctica - Fujita, Shuji; Azuma, Nobuhiko; Fujii, Yoshiyuki; Kameda, Takao; Kamiyama, Kokichi; Motoyama, Hideaki; Narita, Hideki; Shoji, Hitoshi; Watanabe, Okitsugu (2002)
P(論文) From 1993 to 1998,members of the Dome F project group carried out ice coring at Dome F station. They recovered a 2503-m-long ice core. Specific tasks for the ice core processing included (1) core storage, (2) cutting and packing the ice samples for transportation from the station to Japan, and (3) performing initial ice analyses that can be done at the station. In this report we outline the operation and describe our experiences related to the ice core processing to aid similar processing in the future. departmental bulletin paper